Analysis of the Contribution of Agility and Body Flexibility to Dribbling Skills - Eggi Pangestu (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2024)
Purpose of the study: The aim of this research is to determine the contribution of agility and body flexibility to ball dribbling skills. Methodology: This type of research is multiple correlation. The population and sample in this study were 22 people. The research instruments used were an agility test using a shuttle run, a body flexibility test using a sit and reach and a ball dribbling skills test. The data analysis technique used is the multiple correlation value test. Main Findings: Based on the results of the research that has been carried out, the following conclusions can be drawn: (1) There is a contribution of agility to the results of ball dribbling skills with a value of rcount = 0.543 > rtable = 0.423 and a KD value of 29.48%. (2) There is a contribution of body flexibility to the results of ball dribbling skills with a value of rcount = 0.546 > rtable = 0.423 and a KD value of 29.81%. (3) There is a contribution of agility and body flexibility to the results of ball dribbling skills with a value of rcount = 0.696 > rtable = 0.423 and a KD value of 48.44%. Novelty/Originality of this study: With comprehensive analysis methods, this research not only strengthens understanding of the importance of physical training focused on agility and flexibility, but also provides practical insights for coaches in designing more effective training programs.